Pengaruh Kualitas Produk, Harga, Dan Lokasi Terhadap Kepuasan Pelanggan Di Dhelitha Gordyn - Ratmono, Ratmono; Yateno, Yateno; Anggraini, Erika Kiki (Jurnal Manajemen DIVERSIFIKASI, 2023)
Buyers can experience a feeling of satisfaction or disappointment (customer satisfaction) onproduct quality, price and location, thus the purpose of this study is to determine productquality, price and location partially their effect on customer satisfaction at Dhelitha GordynStores, Metro City. The research method uses quantitative methods through observation andquestionnaires in obtaining data to be processed using SPSS version 28 software. Theresearch method in this study is accidental sampling with sample statistics obtained bycustomers from representative respondents. The analytical tool used is multiple linearregression with partial t test decisions, simultaneous f test, and coefficient of determination.The survey results show that if customer satisfaction is met in terms of the quality of theproducts sold, and at a reasonable price, as well as a comfortable and safe environment,customer satisfaction will increase.